Disparity Analysis of Judge’s Decisions of The Crime of Premeditated Murder - febrianti sungo (Universitas Negeri Gorontalo, 2019)
Abstract: This study aims to find out the Disparity analysis of judges' decisions on the crime of premeditated murder in Decision Number 7/Pid.Sus-Anak/PN.Kbj and Decision Number 1/Pid.Sus-Anak/2016/PN.Gto. The method used in this research was normative legal research. The approach used a legal approach or a statute approach and a case approach. The judge in making a decision, of course, first sees whether the act committed by the child is intentional or unintentional so that it can be seen by a judge when enforcing Restitave Justice where one way to move the legal process through the courts is to become a legal settlement outside the court by involving the victim's family as the most important element in the settlement of a crime. However, if you look at the crimes against children that have been committed, diversion efforts are not enforced because the child has committed a very severe crime. The community needs to understand that inequality or disparity is not a bad thing but it is natural for clear legal reasons except arbitrarily, this is normal and is not prohibited by the legal system in Indonesia. The community needs to be informed in advance about the background of the emergence of disparities in decision-making.Keywords: Disparity Analysis, Murder;